GLOBAL AND REGIONAL EPIDEMIOLOGY OF ZOONOTIC DISEASES: A CONTEMPORARY ANALYSIS OF TRANSMISSION PATTERNS AND PUBLIC HEALTH IMPLICATIONS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This study examines the global and regional epidemiology of zoonotic diseases through systematic analysis of surveillance data, outbreak patterns, and transmission dynamics across diverse geographical contexts. The investigation synthesizes contemporary epidemiological evidence to identify critical trends in zoonotic disease emergence, quantify regional burden variations, and evaluate the effectiveness of current surveillance frameworks. Findings reveal substantial regional disparities in disease incidence and mortality, with emerging hotspots linked to ecological disruption and human-animal interface changes.